A Novel Method for Rotor Tracking Using Bipolar Electrogram Phase - Roney,CH; Cantwell,C; Siggers,JH; Ng,FS; Peters,NS (2014)
Assessing the location and stability of electrical rotors can help target ablation therapy for atrial fibrillation. Rotor cores can be tracked by identifying singularities in the phase of spatially distributed electrical recordings. This is routinely applied to unipolar electrogram and action potential data, but not to bipolar electrogram data, which contains local activation only. We developed and tested a technique to track phase singularities from simulated bipolar data. Bipolar electrogram phase was found to be as effective as action potential and as unipolar electrogram phase for rotor tip detection when using simulated data, suggesting that it may be used clinically as an alternative method to unipolar phase to locate rotor phase singularities in atrial fibrillation.